General practitioners' perspectives on care coordination in primary health care: A qualitative study. (December 2018) - Vassbotn, Ane Drougge; Sjøvik, Hege; Tjerbo, Trond; Frich, Jan; Spehar, Ivan
Introduction: To explore Norwegian general practitioners' experiences with care coordination in primary health care. Methods: Qualitative study using data from five focus groups with 32 general practitioners in Norway. We analysed the data using systematic text condensation, a descriptive and explorative method for thematic cross-case analysis of qualitative data. Results: The general practitioners had different notions of care pathways. They expressed a wish and an obligation to be involved in planning and coordination of primary health-care services, but they experienced organisational and financial barriers that limited their involvement and contribution. General practitioners reported lack of information about and few opportunities for involvement in formal coordination initiatives, and they missed informal arenas for dialogue with other primary health-care professionals. They argued that the general practitioner's role as coordinator should be recognised by other parties and that they needed financial compensation for contributions and attendance in meetings with the municipality. Discussion: General practitioners need informal arenas for dialogue with other primary health-care professionals and access to relevant information to promote coordinated care. There might be an untapped potential for improving patient care involving general practitioners more in planning and coordinating services at the system level. Financial compensation of general practitioners contribution may promote increased involvement by general practitioners.